Efficacy and safety of first-line anti-tuberculosis drugs combined with Linezolid for the treatment of pediatric tuberculous meningitis in real-word practice - Ai, T (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To evaluate the efficacy and safety of first-line anti-tuberculosis (TB) drugs combined with linezolid in treatment of children with tuberculous meningitis (TBM). Methods: A retrospective cohort study design was performed. Eight-nine Children diagnosed as TBM during January 1st 2016 and December 31st 2023 in Department of Infectious Disease, Children's Hospital of Chongqing Medical University were enrolled in the study. According to different treatment regimens, children were divided into a group of first-line anti-tuberculous drugs (isoniazid, rifampicin, pyrazinamide, ethambutol (HRZE)) and a group of HRZE and linezolid combination (HRZEL). The efficacy and safety of the 2 regimens were compared and the relationship between linezolid drug concentration and adverse reactions were analyzed. Comparisons between groups were performed using χ2 test and Mann-Whitney U test. Results: The 89 children with TBM included 53 males and 36 females with an onset age of 4.6 (1.4, 9.6) years. There were 27 cases in the HZREL group and 62 cases in the HRZE group. Before treatment, positive rate of interferon-gamma release assays (IGRA) in HRZEL group was lower than that in HRZE group (64% (16/25) vs.92% (55/60), χ2=9.82, P<0.05), but protein level of cerebrospinal fluid (CSF) was higher than that in HRZE group (1.2 (1.0, 2.0) vs.0.8 (0.4,1.4) g/L, Z=0.32, P<0.05). By the end of the intensive phase, there were no significant differences of rates of CSF improvement and etiology negativity between HRZEL group and HRZE group (both P>0.05).The 44 TBM children with high CSF protein (>1 g/L) included 25 males and 19 females with an onset age of 6.7 (3.0, 11.8) years. There were 21 cases in the HZREL group and 23 cases in the HRZE group accordingly. Before treatment, there were no significant differences of positive rate of IGRA test and CSF protein level between the 2 groups (62% (13/21) vs. 87% (20/23), 1.7 (1.1, 2.2) vs. 1.5 (1.2, 1.9) g/L, χ2=3.67, Z=0.23, both P>0.05). There were no significant differences in CSF indicators, etiology negativity or imaging remission between the two groups by the end of intensive phase (all P>0.05). Higher frequencies of granulocytopenia, gastrointestinal symptoms as well as withdrawal or change of drugs were found in HRZEL group when compared to those in HRZE group (44% (12/27) vs. 19% (12/62), 7% (2/27) vs. 0, 33% (9/27) vs. 3% (2/62), χ2=6.01, 4.70, 15.74, all P<0.05). Conclusions: The efficacy of HRZEL regimen is similar to conventional HRZE regimen in children with TBM, but with higher adverse effect. Prudentially evaluating the pros and cons of linezolid in the usage of drug-susceptible TB and carefully monitoring of linezolid associated adverse effects is suggested